2005
DOI: 10.1007/s00534-005-1027-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for massive intraoperative bleeding during laparoscopic splenectomy

Abstract: Careful attention to intraoperative bleeding during laparoscopic splenectomy is necessary for patients with portal hypertension and/or deteriorated liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Splenectomy and partial splenic embolization induce thrombocytosis and improve liver function for more than 6 months in patients with CLD and cirrhosis (Murata et al 1996;Murata et al 2008a). However, patients with CLD and cirrhosis often have splenomegaly and thrombocytopenia and are at high risk for bleeding and complications in operations (Patel et al 2003;Ohta et al 2005). Additionally, partial splenic embolization has various complications, such as ascites, splenic or portal vein thrombosis, splenic abscess, and splenic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Splenectomy and partial splenic embolization induce thrombocytosis and improve liver function for more than 6 months in patients with CLD and cirrhosis (Murata et al 1996;Murata et al 2008a). However, patients with CLD and cirrhosis often have splenomegaly and thrombocytopenia and are at high risk for bleeding and complications in operations (Patel et al 2003;Ohta et al 2005). Additionally, partial splenic embolization has various complications, such as ascites, splenic or portal vein thrombosis, splenic abscess, and splenic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertension with gastric varices increases the risk of intraoperative hemorrhage (LoE 4) [94]. In 2005, Cobb et al [95] studied 50 patients with liver cirrhosis who underwent different laparoscopic procedures in their institution.…”
Section: Limits Of the Laparoscopic Approachmentioning
confidence: 99%
“…In 2005, Ohta et al [94] published an analysis of risk factors for massive intraoperative bleeding ([800 ml) during LS. In the multivariate analysis, portal hypertension and Child class were independent risk factors, whereas univariate analysis showed that significant risk factors are liver cirrhosis, portal hypertension, splenomegaly, Child class, and preoperative platelet count.…”
Section: Limits Of the Laparoscopic Approachmentioning
confidence: 99%
“…Ohta et al adopted a case-control study design to identify portal hypertension and Child class as the independent risk factors for massive bleeding during LS in a multivariate analysis. 33 Kawanaka et al compared characteristics between 11 converted cases and 95 non-converted cases in the setting of liver cirrhosis and portal hypertension, and identified that conversion was significantly related to an exacerbation of liver function and resected spleen weight. 8 Therefore, in addition to the surgeon's extensive experience with laparoscopic surgery, several techniques have been developed to ease the surgical procedure in the literature.…”
Section: Discussionmentioning
confidence: 99%